Residents of Marawi mark Eid al-Adha amid fighting - Maitem, Jeoffrey B. (2017)
Residents of Marawi city who stayed put despite the fighting between soldiers and terrorists in the city trooped to mosques to celebrate Eid al-Adha or Day of Sacrifice, a key Muslim holiday.
Keywords: Marawi War; Eid Al-Adha